1992
DOI: 10.1128/iai.60.12.5232-5241.1992
|View full text |Cite
|
Sign up to set email alerts
|

Histological and immunocytochemical characterization of Coxiella burnetii-associated lesions in the murine uterus and placenta

Abstract: The fetoplacental units and the postgravid uterus of BALB/cJ (H-2d) mice inoculated intraperitoneally with Coxiella burnetii (Nine Mile isolate, phase I) on day 6 of pregnancy were examined histologically and immunocytochemically at 1 to 160 days postinoculation. Clinically, abortions, stillbirths, and perinatal deaths were observed. Histological lesions in the placenta were characterized by severe necrosis of the decidua basalis and the labyrinth, fibrinoid degeneration of decidual vessels, and microthrombosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(8 citation statements)
references
References 36 publications
1
7
0
Order By: Relevance
“…A very similar occurrence has been observed with Coxiella burnetii, where hepatic lesions have been found in fetus from naturally infected sheep (27); however, Baumgärtner and Bachmann in an extensive immunohistochemical study (4) found no positive immunoreaction or lesions in the fetuses of experimentally infected pregnant mice but found both lesions and positive immunoreaction in surviving 9-day-old offspring, which suggests that fetal infection occurred just before or after birth.…”
Section: Discussionsupporting
confidence: 71%
“…A very similar occurrence has been observed with Coxiella burnetii, where hepatic lesions have been found in fetus from naturally infected sheep (27); however, Baumgärtner and Bachmann in an extensive immunohistochemical study (4) found no positive immunoreaction or lesions in the fetuses of experimentally infected pregnant mice but found both lesions and positive immunoreaction in surviving 9-day-old offspring, which suggests that fetal infection occurred just before or after birth.…”
Section: Discussionsupporting
confidence: 71%
“…The involvement of the epididymis in metastatic dissemination of N. gonorrhoeae to the semen is characteristic of chronic infection (5). C bumetii-associated lesions have been observed in hu-0 0 0 0 0 mans and in experimentally infected female mice (4,17,28,34). In patients with interstitial pneumonitis, researchers have found necrotic foci in the alveolar walls, small granulomas in the spleen and liver, and focal perivascular inflam-_ matory infiltrations in many other organs (28,34).…”
Section: Discussionmentioning
confidence: 99%
“…It could be that failure of this mechanism determines abortion or stillbirth. Studies performed in mice (Baumga¨rtner and Bachmann 1992) suggest that foetus-placental union resists C. burnetii vertical infection and that the infection of the newborn is established by aerosol inhalation at the moment of parturition. In contrast, if vertical transmission is possible, this could be an indication of persistent infection due to immune tolerance to an early in utero infection, as proposed for other infections such as bovine viral diarrhoea virus (Houe et al 1995) or Mycobacterium avium subsp.…”
Section: Calvesmentioning
confidence: 99%